2012
DOI: 10.1200/jco.2011.36.8571
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Chemotherapy-Induced Structural Changes in Cerebral White Matter and Its Correlation With Impaired Cognitive Functioning

Abstract: We report evidence of longitudinal changes in cognitive functioning and cerebral WM integrity after chemotherapy as well as an association between both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
257
6
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(303 citation statements)
references
References 51 publications
21
257
6
13
Order By: Relevance
“…Magnetic resonance imaging studies have demonstrated lower integrity of cerebral white matter (location of myelinated axons) rather than gray matter (location of neuronal cell bodies) in patients with CICI than in healthy subjects (10)(11)(12). However, these findings do not directly indicate whether the decreased integrity of the cerebral white matter is caused by damage to axons themselves, which are the main components of white matter, or by Wallerian axonal degeneration following neuronal damage.…”
Section: Introductioncontrasting
confidence: 43%
“…Magnetic resonance imaging studies have demonstrated lower integrity of cerebral white matter (location of myelinated axons) rather than gray matter (location of neuronal cell bodies) in patients with CICI than in healthy subjects (10)(11)(12). However, these findings do not directly indicate whether the decreased integrity of the cerebral white matter is caused by damage to axons themselves, which are the main components of white matter, or by Wallerian axonal degeneration following neuronal damage.…”
Section: Introductioncontrasting
confidence: 43%
“…Taken together, these findings suggest that this injury may begin quite early in the disease course but is more affected chronically and/or by adjuvant treatments. Regional clustering and Hurst exponent results indicate a widespread effect, consistent with previous studies (Deprez et al., 2012; Kesler et al., 2015). Frontal, parietal, and temporal areas were altered in the breast cancer group compared to controls, consistent with deficits in memory, executive function, and verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the biological basis for this syndrome, nor the predictors, nor any interventions, are well understood although recent investigations suggest a relationship with structural changes occurring in cerebral white matter and several investigations are underway. 135,136 While much of the prior work has focused on the effects of chemotherapy, ET may also adversely affect cognition, [137][138][139][140] although few specific investigations have been conducted and none in young women. In the ZIPP trial (6 cycles of CMF ± 2 years of goserelin, goserelin plus tamoxifen, or tamoxifen), no effect of treatment on patients' selfevaluation of memory and concentration was shown.…”
Section: Brca Mutation Carriers (Table 8)mentioning
confidence: 99%